samGlobal Environmental Resources The Ozone Problem (Allokation im marktwirtschaftlichen System, 1983)
This volume contains two papers which use the ozone problem as the empirical starting of their analysis. Gladwin/Ugelow/Walter survey empirically the sectors of the economy which produce fluorcarbons. The regional origin of fluorcarbons in the world and possible international ozone management strategies (e.g. interactions between the USA and Europe) are discussed. Pethig attacks the issue of ozone management from a theoretical aspect and uses game theory in order to discuss potential solutions.